PENGARUH INFLUENCER DAN CONSUMER REVIEW TERHADAP PURCHASE INTENTION DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING - Iqbal Muhammad Alghiffari; Sari Listyorini; Widiartanto Widiartanto (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2022)
The era of digital technology gave rise to the phenomenon of product marketing using influencers and consumer reviews based on social media and e-commerce. Both are new determinants besides a brand image that affect purchase intention. This study aims to examine the influence of influencers and consumer reviews on purchase intention in relation to the brand image of the Compass brand of sneakers. The research approach is quantitative with an instrument in the form of a questionnaire distributed to 400 sample respondents via social media WhatsApp. The collected data were analyzed using the Partial Least Square (PLS) technique using the Structural Equation Model (SEM). The results showed that: influencers, consumer reviews, and brand image had a significant effect on purchase intention. Influencers and consumer reviews have a significant effect on brand image, and brand image is proven to act as an intervening variable that mediates the influence of influencers on purchase intention but is not proven as an intervening variable from consumer reviews. Era teknologi digital memunculkan fenomena pemasaran produk menggunakan influencer dan consumer review yang berbasis media sosial dan e-commerce. Keduanya menjadi faktor determinan baru selain brand image yang mempengaruhi purchase intention. Studi ini bertujuan mengkaji tentang pengaruh dari influencer dan consumer review terhadap purchase intention dalam kaitannya dengan brand image dari produk sepatu sneakers bermerek Compass. Pendekatan penelitian adalah kuantitatif dengan instrumen berupa kuesioner yang disebarkan kepada 400 responden sampel melalui media sosial Whatsapp. Data yang terkumpul dianalisis dengan teknik Partial Least Square (PLS) menggunakan Structural Equation Model (SEM). Hasil penelitian menunjukkan bahwa: influencer, consumer review, dan brand image berpengaruh signifikan terhadap purchase intention. Influencer dan consumer review berpengaruh signifikan terhadap brand image, dan brand image terbukti berperan sebagai variabel intervening yang memediasi pengaruh dari influencer terhadap purchase intention tetapi tidak terbukti sebagai variabel intervening dari consumer review.